A Morphological Transition of Inverse Mesophases of a Branched‐Linear Block Copolymer Guided by Using Cosolvents1. Issue 36 (15th July 2015) - La, Yunju; An, Tae Hyun; Shin, Tae Joo; Park, Chiyoung; Kim, Kyoung Taek
Abstract We report here a strategy for influencing the phase and lattice of the inverse mesophases of a single branched‐linear block copolymer (BCP) in solution which does not require changing the structure of the BCP. The phase of the self‐assembled structures of the block copolymer can be controlled ranging from bilayer structures of positive curvature (polymersomes) to inverse mesophases (triply periodic minimal surfaces and inverse hexagonal structures) by adjusting the solvent used for self‐assembly. By using solvent mixtures to dissolve the block copolymer we were able to systematically change the affinity of the solvent toward the polystyrene block, which resulted in the formation of inverse mesophases with the desired lattice by self‐assembly of a single branched‐linear block copolymer. Our method was also applied to a new solution self‐assembly method for a branched‐linear block copolymer on a stationary substrate under humidity, which resulted in the formation of large mesoporous films. Our results constitute the first controlled transition of the inverse mesophases of block copolymers by adjusting the solvent composition.